Parametric decay of current‐driven Langmuir waves in plateau plasmas: Relevance to solar wind and foreshock events. Issue 7 (25th July 2017) - Sauer, Konrad; Malaspina, David M.; Pulupa, Marc; Salem, Chadi S.
Abstract: Langmuir amplitude modulation in association with type III radio bursts is a well‐known phenomenon since the beginning of space observations. It is commonly attributed to the superposition of beam‐excited Langmuir waves and their backscattered counterparts as a result of parametric decay. The dilemma, however, is the discrepancy between fast beam relaxation and long‐lasting Langmuir wave activity. Instead of starting with an unstable electron beam, our focus in this paper is on the nonlinear response of Langmuir oscillations that are driven after beam stabilization by the still persisting current of the (stable) two‐electron plasma. The velocity distribution function of the second population forms a plateau (index h ) with a point at which ∂ f h ∂v ∼ 0 associated with weak damping over a more or less extended wave number range k . As shown by particle‐in‐cell simulations, this so‐called plateau plasma drives primarily Langmuir oscillations at the plasma frequency ( ω e ) with k = 0 over long times without remarkable change of the distribution function. These Langmuir oscillations act as a pump wave for parametric decay by which an electron‐acoustic wave slightly below ω e and a counterstreaming ion‐acoustic wave are generated. Both high‐frequency waves have nearly the same amplitude, which is given by the product of plateau density and velocity. Beating of these two wave types leads to pronounced Langmuir amplitude modulation, in reasonable agreement with solar wind and terrestrial foreshock observations made by the Wind spacecraft. Key Points: Particle simulations show current‐driven Langmuir oscillations in plateau plasmas remaining after beam relaxation Langmuir oscillations at the electron plasma frequency decay into a Langmuir wave and a counterpropagating ion‐acoustic wave Wave decay in plateau plasmas to Langmuir waves with double‐peak spectra in the solar wind, as seen in spacecraft measurements